2017
DOI: 10.1021/acs.biomac.6b01688
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Microenvironment-Sensitive Liposomes Penetrate Tumor Tissue via Attenuated Interaction of the Extracellular Matrix and Tumor Cells and Accompanying Actin Depolymerization

Abstract: Delivery of anticancer drugs into tumor cores comprised of malignant cancer cells can result in potent therapeutic effects. However, conventional nanoparticle-based drug delivery systems used for cancer therapy often exhibit inefficient tumor-penetrating properties, thus, suggesting the need to improve the functional design of such systems. Herein, we focus on the interactions between cancer cells and the extracellular matrix (ECM) and demonstrate that liposomes modified with slightly acidic pH-sensitive pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…The effect of surface charge on penetration can be used to control the diffusion by using surface switches such as a pH‐responsive peptide that can turn negatively charged nanoparticles to positively charged ones in slightly acidic conditions. The underlying idea is that the negatively charged nanoparticles will penetrate into the spheroid and, once surrounded by an acidic environment, the nanoparticles displayed a positive charge accelerating the uptake by cells . This required the movement of NPs in the paracellular route in contrast to the transcellular route, which the authors confirmed by observing the actin depolymerization.…”
Section: Using Mcts To Evaluate Nano Drug Carriersmentioning
confidence: 94%
See 1 more Smart Citation
“…The effect of surface charge on penetration can be used to control the diffusion by using surface switches such as a pH‐responsive peptide that can turn negatively charged nanoparticles to positively charged ones in slightly acidic conditions. The underlying idea is that the negatively charged nanoparticles will penetrate into the spheroid and, once surrounded by an acidic environment, the nanoparticles displayed a positive charge accelerating the uptake by cells . This required the movement of NPs in the paracellular route in contrast to the transcellular route, which the authors confirmed by observing the actin depolymerization.…”
Section: Using Mcts To Evaluate Nano Drug Carriersmentioning
confidence: 94%
“…While neutral liposomes did not associate with the spheroid, cationic liposomes did accumulate on the spheroid periphery. Only negative charged liposomes were found to display sufficient penetration into the B16−F1 spheroids . An important study and theoretical model to explain this behavior was published by Reddy et al Although spheroids were not used, the researchers have attempted to answer the question how size, shape and charge affect the transport in interstitial fluid.…”
Section: Using Mcts To Evaluate Nano Drug Carriersmentioning
confidence: 99%
“…The high collagen level in the tumor ECM is a major barrier in the transport of NPs, while LOX could crosslink collagen and stiffens the ECM, which further deteriorates the effective transport and penetration of the NPs. Furthermore, the ECM network is composed of charged matrix polymers, such as collagen and hyaluronan, which hinder delivery of highly charged NPs on account of electrostatic interactions with these matrix polymers (Lieleg, Baumgärtel, & Bausch, ; Stylianopoulos et al, ; Suzuki et al, ).…”
Section: Factors Affect Tumor Penetration Of Npsmentioning
confidence: 99%
“…However, with remarkable advancement in technology and analytical methods seen in the last decade, attention has shifted to the TM contribution towards the development of chemoresistance [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Chemotherapeutic drugs need to access all cancer cells in a solid tumor to be effective, thus components of the tumor microenvironment become important players in the response of these cells to drugs [ 33 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. The TM is a dynamic entity and is characterized by cellular heterogeneous, the amounts of oxygen, nutrients and ECM proteins [ 41 , 54 , 55 , 56 , 57 , 58 , 59 ].…”
Section: Introductionmentioning
confidence: 99%